2009
DOI: 10.1111/j.1399-302x.2009.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mouse prolactin‐inducible protein in saliva on the aggregation of oral bacteria

Abstract: In this study it was confirmed that mPIP plays a role in the aggregation of oral bacteria. The salivary components promoting aggregation of oral bacteria are considered to be part of the oral defense mechanisms so these findings provide insight into a possible function of mPIP in host defense by promoting aggregation of oral bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…These include the small salivary mucin‐7 (MUC7) (MG2), which promotes bacterial agglutination, surfactant protein‐A, proline‐rich proteins, prolactin‐inducible protein and β ‐2‐microglobulin, which is notably present in most (82%) biopsies from aggressive periodontitis patients but largely absent from normal controls and chronic severe periodontitis specimens (Syrjanen et al 1985). Saliva from prolactin‐inducible protein‐knock‐out mice exhibit significantly lower agglutination of oral bacteria than saliva from wild‐type control mice, suggesting that prolactin‐inducible protein contributes to host‐defense of the oral cavity by agglutinating oral bacteria (Nistor et al 2009). The salivary agglutinin/ GP340 / Deleted in Malignant Brain Tumors‐1 ( DMBT1 ) is a large glycoprotein that contains multiple scavenger receptor cysteine‐rich repeats.…”
Section: Functional Families Of Antimicrobial Proteins In the Oral Camentioning
confidence: 99%
“…These include the small salivary mucin‐7 (MUC7) (MG2), which promotes bacterial agglutination, surfactant protein‐A, proline‐rich proteins, prolactin‐inducible protein and β ‐2‐microglobulin, which is notably present in most (82%) biopsies from aggressive periodontitis patients but largely absent from normal controls and chronic severe periodontitis specimens (Syrjanen et al 1985). Saliva from prolactin‐inducible protein‐knock‐out mice exhibit significantly lower agglutination of oral bacteria than saliva from wild‐type control mice, suggesting that prolactin‐inducible protein contributes to host‐defense of the oral cavity by agglutinating oral bacteria (Nistor et al 2009). The salivary agglutinin/ GP340 / Deleted in Malignant Brain Tumors‐1 ( DMBT1 ) is a large glycoprotein that contains multiple scavenger receptor cysteine‐rich repeats.…”
Section: Functional Families Of Antimicrobial Proteins In the Oral Camentioning
confidence: 99%
“…Of particular interest is the prolactin inducible protein, Pip, a protein first identified by us and shown to be highly abundant in both mouse and human saliva [21,22], and was found to be abundant in all 4 saliva sample pools (2 female pools, 2 male pools). We have previously shown that Pip can aggregate oral bacteria [23] inhibiting their activity. Further, using a Pip knockout mouse model we demonstrated that loss of Pip function had significant effects on both the diversity of the oral flora and abundance of specific bacteria of the oral cavity of the Pip null mouse [24].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding prolactin-induced proteins, they were observed in higher abundance in 2-DE and in the whole extract of dental biofilm formed in the presence of monosaccharides than in the control and sucrose groups. These proteins are involved in bacterial aggregation [Nistor et al , 2009], and the reason why treatment with the mixture of glucose and fructose allowed the maintenance of these proteins, either by less processing by bacteria or due to the presence of new binding sites for protein in the dental biofilm, requires further studies.…”
Section: Resultsmentioning
confidence: 99%